Identification of linear epitopes in SjSP-13 of Schistosoma japonicum using a GST-peptide fusion protein microplate array - Ma, Li (Parasit Vectors, 2019)
BACKGROUND: The identification and characterization of epitopes facilitate the discovery and development of new therapeutics, vaccines and diagnostics for infectious diseases. In this study, we developed a glutathione S-transferase (GST)-peptide fusion protein microplate array for the identification of linear B-cell epitopes and applied this novel method to the identification of linear B-cell epitopes of SjSP-13, an immunodiagnostic biomarker of schistosomiasis japonica. METHODS: SjSP-13 was divided into 17 overlapped peptides (p1-17), and the coding sequence of each peptide was obtained by annealing two complementary oligonucleotides. SjSP-13 peptides were expressed by fusion with an N-terminal GST tag and a C-terminal 6xHis tag. The GST-peptide-His fusion protein was specifically bound to the Immobilizer Glutathione MicroWell 96-well plates without purification. SjSP-13 peptides and core epitopes that could be recognized by sera from schistosomiasis patients were identified by ELISA and confirmed by Western blot analysis. The receiver operating characteristic (ROC) analysis was performed to determine the diagnostic validity of the identified peptide. RESULTS: Full-length GST-peptide-His fusion proteins were successfully expressed and specifically bound to the Immobilizer Glutathione MicroWell 96-well plates. Two adjacent peptides (p7 and p8) were found to be highly immunogenic in humans. The core epitope of p7 and p8 is an 11-aa peptide ((80)KCLDVTDNLPE(90)) and an 8-aa peptide ((90)EKIIQFAE(97)), respectively. The area under the ROC curve (AUC) value of the peptide which contains the two identified epitopes is 0.947 ± 0.019. The diagnostic sensitivity and specificity of the peptide is 76.7% (95% CI: 68.8–84.5%) and 100%, respectively. CONCLUSIONS: (90)EKIIQFAE(97) and (80)KCLDVTDNLPE(90) are the two linear epitopes of SjSP-13 recognized by patient sera, and could be potential serological markers for schistosomiasis japonica. [Image: see text]